Ecological tourism suitability evaluation and landscape ecological risk analysis of the Yangtze River Delta Region from 2000 to 2020 based on the MaxEnt model - Junjie Li; Xiaodong Liu; Yonggang Wang; Xiangbin Peng; Huanchen Tang; Maoguo Li (Journal of Asian Architecture and Building Engineering)
This study aims to assess the changes in ecotourism suitability (ETS) in the Yangtze River Delta (YRD) and reveal the underlying ecological carrying capacity and potential risks, offering significant academic and practical value. Using multisource spatial data from 2000 to 2020 and incorporating 14 variables such as the natural environment, human activities, and climate conditions, an ETS evaluation system is constructed. The study employs the Maximum Entropy model (MaxEnt) to simulate spatiotemporal evolution and uses the Landscape Pattern (LP) index and Landscape Ecological Risk (LER) evaluation model to explore the spatial correlation between ETS and ecological risk. The results show: (1) ETS exhibits clear spatial differentiation in the YRD, with higher suitability in the central and eastern regions, and lower suitability in the west. Over the 20-year period, 60.10% of the area remained stable, 16.70% increased, and 23.20% decreased; (2) LP indicates increased fragmentation and enhanced diversity, with decreased connectivity of ecological patches; (3) LER overall increased, with more medium-risk areas; (4) After 2005, a significant spatial coupling between ETS and LER emerged, with some areas showing a “high suitability – high risk” pattern, indicating ecological pressure. The findings provide scientific evidence for the development of YRD’s ecotourism resources and sustainable planning.